1971
DOI: 10.3181/00379727-137-35549
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Effects of Amphotericin B

Abstract: Administration of the polyene antibiotic, Amphotericin B (AmB) for the treatment of mycotic diseases has been associated with abnormalities of renal function (1). Its chronic administration in man causes a reduction in glomerular filtration rate (GFR) and effective renal plasma flow (ERPF) , renal tubular acidosis, natriuresis, and kaliuresis (2). In the dog, acute administration of AmB results in a similar decrease in GFR and E R P F apparently due to active renal arteriolar constriction ( 3 ) . Studies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Although amphotericin B-related renal abnormalities are generally reversible, a minority of patients may develop irreversible renal dysfunction [12]. The nephrotoxicity of CAB is believed to result from a combination of vascular and direct tubular effects [13][14][15]. Infusion of CAB can produce an acute decrease in renal blood flow and glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although amphotericin B-related renal abnormalities are generally reversible, a minority of patients may develop irreversible renal dysfunction [12]. The nephrotoxicity of CAB is believed to result from a combination of vascular and direct tubular effects [13][14][15]. Infusion of CAB can produce an acute decrease in renal blood flow and glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, rats given repeated injections of amphotericin B developed polyuria, hypostheruria, distal tubular renal acidosis, and potassium wasting. In a complementary study Jose et al (1971) reported a decrease in free water clearance following amphotericin B which was independent of either altered glomerular filtration rate or distal sodium delivery. The later finding is compatible with amphotericin B inducing increased membrane permeability to water at a distal nephron/ collecting duct site.…”
Section: George a Portermentioning
confidence: 99%
“…Renal complica¬ tions include disturbed urinary dilution and concentra¬ tion,1,2 renal tubular acidosis,3 impaired sodium and potas¬ sium conservation,1,4 and both acute and chronic renal failure. 1,4,5 Although rat6 and canine7 models have demonstrated immediate depression of both whole kidney and single nephron glomerular filtration rate (GFR) after exposure to amphotericin, the onset of impaired renal function in hu¬ mans typically does not develop until several days after the initiation of amphotericin therapy.3,8 Immediate acute renal failure (ARF) following amphotericin administration has not previously been reported in humans. We describe a patient with long-standing cryptogenic cirrhosis of the liver who had recurrent, immediate acute renal failure with each of four attempts to administer amphotericin.…”
mentioning
confidence: 99%